HUBUNGAN KEPADATAN HUNIAN DAN KEBIASAAN MEROKOK DALAM RUMAH DENGAN KEJADIAN ISPA PADA BALITA DI DESA PASREPAN KABUPATEN PASURUAN - Fiddaroini, Fakhrun Nisa'; Nanang Bagus Sasmito; Primanda Ardhiansyah (Nursing Sciences Journal, 2025)
Acute Respiratory Infection (ARIs) is one of the causes of death in children. The incidence of ARI in toddlers can occur due to several risk factors such as home occupancy density, home ventilation, and smoking habits of family members. This research aimed to determine the relationship between occupancy density and smoking habits in the house with the incidence of ARI in toddlers in Pasrepan Village, Pasuruan Regency. This study employed a quantitative approach with a cross-sectional design. The sample consisted of 35 respondents selected using a total sampling technique. Instruments of occupancy density, smoking habits, and ARI incidence were studied using questionnaires and chi-square statistical tests. The results showed that more than half of the respondents (57.1%) lived in overcrowded homes, and a similar proportion (57.1%) had smoking habits in the house. The incidence of ARI was reported in more than half of the respondents (54.3%). The results showed that more than half of the residential density did not meet the requirements, with as many as 20 respondents (57.1%). Having a smoking habit in the house, more than half as many as 20 respondents (57.1%). The incidence of ARI, more than half as many with 26 respondents (54.3%) experiencing ARI. The results of the chi-square test found that there was a relationship between occupancy density (p-value = 0.0001) and smoking habits in the house (p-value = 0.025) with the incidence of ARI in toddlers in Pasrepan Village, Pasuruan Regency. Nurses are expected to further increase socialisation to provide education related to a qualified environment and the dangers of smoking in the house to mothers who have toddlers.